Can Hoarding Be a Symptom of Social Anxiety Disorder? A Case Study. (October 2013) - Vigne, Paula; De Menezes, Gabriela B.; Yücel, Murat; Fontenelle, Leonardo F.
Background: Hoarding is defined as the excessive collection and failure to discard possessions of apparently little value, leading to clutter, distress, and disability. Although patients with hoarding typically may feel ludicrous for not discarding useless, and sometimes bizarre, possessions, we are not aware of any previous description of patients displaying hoarding as a result of social anxiety. Method: Single case report. Results: In this article, we describe a patient with severe social anxiety disorder who displayed hoarding as a direct consequence of social anxiety-related beliefs and atypical safety behaviors. Conclusions: This case is of particular interest to current debates concerning the status of hoarding in new versions of classificatory systems. It also indicates that social anxiety disorder should be included in the list of conditions that needs to be excluded in order to diagnose "primary" hoarding disorder.